Մշակոյթին եւ կրօնին փոխ յարաբերման հարցը Հայ Աւետարանական եկեղեցւոյ մէջ - Յարութիւն Սելիմեան (ՀՀ ԳԱԱ հրատ.)
В первой половине XIX в. духовно-культурная переориентация шла в сторону национального самосознания армянского народа, и это ярко проявлялось в патриотических настроениях духовного творчества авторов-романтиков того периода (М. Налбандян, Р. Патканян, И. Шаазиз). In the first half of the 19th century, the spiritual-cultural reorientation was efficiently taking place. The growth of national self-consciousness was more and more reflected in the writings of the Romantics.
Keywords: Religion; Geography; Anthropology; Recreation; Culture and Cultural Processes